Introduction to the Special Issue on Emotions in Reading, Learning, and Communication. Issue 1 (7th February 2022) - Bohn-Gettler, Catherine M.; Kaakinen, Johanna K.
ABSTRACT: In our current era, learners are confronted with many and varying sources of information, such as news media, books, websites, social media, scientific articles, communicative interactions, and more. In addition, individuals must learn from such sources, making it important to critically examine the factors underlying learning from text and discourse. Importantly, the valence and activation of readers' emotions can influence the quality of readers' processing, which could help or hinder the learner's ability to understand and learn from text related to important issues. Although theoretical and empirical work documents the role of emotions in learning and motivation, reading- and discourse-specific models are needed. At present, the literature examining reading presents conflicting findings related to the influence of emotion on textual processing. However, asproposed in the Process, Emotion, Task (PET) framework, the discrepant findings related to reading processes may be explained by interactions between specific reader emotions and the type of task. Hence, examining both emotions and features of the text are critical when considering how to support readers' ability to comprehend, evaluate, and learn from text. This article introduces a special issue of Discourse Processes that brings together experts engaging in empirical studies on how emotion influences learning and processing for varying text types in different contexts. Our goal is to further work toward developing a more cohesive understanding of the influence of reader emotions in supporting learning, comprehension, processing, and conceptual change and to draw important connections to the broader fields of text and discourse, learning, and motivation. Such connections are critical for improving learning experiences across a variety of settings and enhancing the relevance of discourse-processing research.